Teaching listening comprehension - Ur, Penny (New York : Cambridge University Press, 1984)
A guide to developing listening comprehension skills in the language classroom that defines the characteristics of real-life listening, analyzes the problems encountered by language learners, and discusses the issues related to planning successful classroom listening practice.
Includes bibliographical references (p. 169-172) and index.
Professional
Keywords: Attention; Comprehension; Listening comprehension; Listening -- Study and teaching; Attention; Listening -- Study and teaching; Psychology of learning